Neuroeducation in Moroccan Secondary Schools: Teachers’ Perceptions, Practices, and Challenges in Life and Earth Sciences - Salma Lafdi; Aafaf Essedaoui; Ihsane Kouchou; Sabah Selmaoui (European Scientific Journal, ESJ, 2026)
Neuroeducation, at the intersection of neuroscience, cognitive psychology, and pedagogy, offers approaches based on brain function to optimize learning conditions in schools. It provides concrete tools to strengthen learners' attention, memory, and motivation. In Morocco, despite efforts to improve the quality of teaching and learner achievement in various scientific disciplines, numerous studies show that major difficulties persist, namely cognitive obstacles such as limited abstract thinking skills and problems with attention and memory(Chakour et al., 2019). Faced with this situation, research shows that knowledge from the neuroscience of learning can inform concrete pedagogical choices, helping teachers understand how attention, memory, and motivation work, and transforming the way teaching sequences are organized to better take into account the diversity of profiles.(Schwartz et al., 2019). In this context, this study examines Moroccan life and earth science teachers' perceptions of the potential contribution of neuroeducational techniques to improving secondary school students' engagement and understanding. To this end, a questionnaire survey was conducted among SVT teachers in Morocco (N=71) to collect data on their perceptions, practices, and needs for improvement. The results indicate a positive perception of these approaches, with approximately 81% agreeing with the effectiveness of neuroeducational techniques, but their application is still limited by organizational and structural constraints.